Developing expertise, customising sleep, enhancing study practices: exploring the legitimisation of modafinil use within the accounts of UK undergraduate students - Steward, Alice (Drugs (Abingdon Engl), 2019)
Introduction and aim: Increasing numbers of students are reportedly using prescription medications to enhance cognition. This study aimed to generate qualitative data on UK students’ understandings and perspectives of the risks and benefits surrounding so-called ‘study drugs’ (particularly, modafinil). Design and methods: Fifteen undergraduate students studying biomedical science subjects were interviewed about their perspectives on study drugs. Interviews were recorded and transcribed for thematic analysis. Users and non-users were included in the sample. Results: The prescription status and comparisons to other legal and illicit stimulants informed accounts of the (lack of) risks associated with study drugs, legitimising use. The customisation of sleep(iness) and wakefulness was described as a key benefit of study drug use. Drivers of use related to university pressures and desires to increase productivity. In periods of heightened stress, such as examinations, students reported altered practices and perspectives on risk. Discussion and conclusions: We noted the contextual nature of students’ use and risk appraisals, with fluctuating social contexts and pressures over time being capable of altering prior assessments and current practices (including the legitimisation of study drug consumption). Further, we highlighted the degree to which students leveraged their biomedical and experiential expertise to account for drug consumption.